2008
DOI: 10.1176/appi.ps.59.10.1155
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists' Role in Depression Care: A Survey of Attitudes, Current Practices, and Barriers

Abstract: For pharmacists to effectively take up depression care, perceived barriers need to be addressed through specific training programs and increased cooperation with general practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
94
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(101 citation statements)
references
References 0 publications
6
94
0
1
Order By: Relevance
“…8,9,11 Pharmacists report positive attitudes regarding providing mental health medication information, discussing options for managing adverse effects, and assessing patient knowledge and understanding of their disease state. 12,13 Yet, despite positive attitudes towards providing pharmacy services to patients with mental illness, pharmacists report low rates of actual service provision. 12,[14][15][16] Pharmacists are significantly more willing to provide pharmacy services to patients with physical illness conditions (eg, asthma, cardiovascular disease) than those with mental illness, 12,[14][15][16] which may be an indicator of mental health stigma (MHS).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9,11 Pharmacists report positive attitudes regarding providing mental health medication information, discussing options for managing adverse effects, and assessing patient knowledge and understanding of their disease state. 12,13 Yet, despite positive attitudes towards providing pharmacy services to patients with mental illness, pharmacists report low rates of actual service provision. 12,[14][15][16] Pharmacists are significantly more willing to provide pharmacy services to patients with physical illness conditions (eg, asthma, cardiovascular disease) than those with mental illness, 12,[14][15][16] which may be an indicator of mental health stigma (MHS).…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Yet, despite positive attitudes towards providing pharmacy services to patients with mental illness, pharmacists report low rates of actual service provision. 12,[14][15][16] Pharmacists are significantly more willing to provide pharmacy services to patients with physical illness conditions (eg, asthma, cardiovascular disease) than those with mental illness, 12,[14][15][16] which may be an indicator of mental health stigma (MHS). In addition, studies have shown that pharmacists have high levels of social distance (ie, unwillingness to interact) and possess stereotypical beliefs about patients with mental illness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The lack of mental health pharmacy education has been described as the main barrier to successful provision of pharmaceutical services for consumers with a mental illness. 15 The World Health Organization recognizes that good communication skills are essential for all health care workers engaged in mental health care. 16 The Australian Pharmacy Council (APC) developed a set of professional capabilities expected of pharmacists in the provision of mental health care.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, STARZ-DRP Form allows the trained CPs to communicate with GPs about their referral patients, using common pharmaceutical language, eliminating language barriers between CPs and GPs. Therefore, STARZ-DRP Form is answering to the several barriers indicated in previous studies including lack of standard model for CPs to perform [39,[45][46][47] and lack of collaboration with GPs [26,38,39,48,49].…”
Section: Nordin Et Almentioning
confidence: 99%